Reduksi Pemborosan Menggunakan Pendekatan Lean Manufacturing pada Lantai Produksi Pembuatan Brake Hose - Firman Ahmad Fauzi; Amaranti, Reni (UNISBA Press, 2024)
Abstract. Waste that occurs on the production floor can hinder the production process and reduce company productivity. The purpose of this study was to identify and reduce waste that occurs on the production floor of brake hoses at PT Nichirin Indonesia. The study used a lean manufacturing approach with several tools such as Value Stream Mapping (VSM), SIPOC diagrams, Pareto charts, cause and effect diagrams, and Failure Mode and Effect Analysis (FMEA). The results showed that there are four types of waste that occur on the production floor, namely waiting time waste, inventory waste, transportation waste, and defective product waste. Waiting time waste and defective product waste are the two most dominant types of waste. Waiting time waste is caused by several factors, including raw materials (rubber) that are not immediately produced, waiting time for stamping machine repairs, and operators in the insert wire clamp process being idle while waiting for the marking process. The defective product waste is caused by the operator's lack of skill in installing the hose on the jig. The proposed improvements to reduce waiting time waste include implementing the 5S work culture, performing preventive maintenance on the stamping machine, and creating visual control for machine maintenance. To reduce the number of defective products, it is recommended to provide routine training to operators to better understand the process and work methods in the trimming hose process. By implementing these proposed improvements, it is expected that the Total Lead Time (TLT) can be reduced by 3.19% and the Process Cycle Efficiency (PCE) can be increased by 3,21%. Abstrak. Pemborosan yang terjadi di lantai produksi dapat menghambat proses produksi dan mengurangi produktivitas perusahaan. Penelitian ini bertujuan untuk mengidentifikasi dan mengurangi pemborosan yang terjadi pada lantai produksi pembuatan brake hose di PT Nichirin Indonesia. Penelitian ini menggunakan pendekatan lean manufacturing dengan beberapa alat seperti Value Stream Mapping (VSM), diagram SIPOC, diagram Pareto, diagram sebab-akibat, dan Failure Mode and Effect Analysis (FMEA). Hasil penelitian menunjukkan bahwa terdapat empat jenis pemborosan yang terjadi di lantai produksi, yaitu pemborosan waktu menunggu, inventory, transportasi, dan produk cacat. Pemborosan waktu menunggu dan produk cacat merupakan dua pemborosan yang paling dominan. Pemborosan waktu menunggu disebabkan oleh beberapa faktor, antara lain bahan baku (rubber) yang tidak segera diproduksi, waktu menunggu perbaikan mesin stamping, dan operator pada proses insert wire clamp yang menganggur karena menunggu proses marking. Sedangkan pemborosan produk cacat disebabkan oleh kurang terampilnya operator dalam memasang hose pada jig. Usulan perbaikan yang diberikan untuk mengurangi pemborosan waktu menunggu adalah dengan menerapkan budaya kerja 5S, melakukan preventive maintenance pada mesin stamping, dan membuat visual control untuk perawatan mesin. Sedangkan untuk mengurangi jumlah produk cacat, disarankan untuk mengadakan pelatihan rutin kepada operator agar lebih memahami proses dan cara kerja pada proses trimming hose. Dengan menerapkan usulan perbaikan ini, diharapkan Total Lead Time (TLT) dapat berkurang sebesar 3,19% dan Process Cycle Efficiency (PCE) dapat meningkat sebesar 3,21%.